Systematic review of integration of neonatal and child health interventions with pediatric HIV interventions - Brianna L Smith, MIA; Sara Sara Zizzo, MPH; Anouk Amzel, MD, MPH; Sarah Wiant, MPH; Molly C. Pezzulo, MPH; Sarah Konopka, MA; Rachel Golin, MD, MHS; Alexandra C. Vrazo, PhD, MPH (Global Health and Education Projects, Inc., 2018)
Background/Objectives: In the last decade, many strategies have called for integration of HIV and child survival platforms to reduce missed opportunities and improve child health outcomes. Countries with generalized HIV epidemics have been encouraged to optimize each clinical encounter to bend the HIV epidemic curve. This systematic review looks at integrated child health services and summarizes evidence on their health outcomes, service uptake, acceptability, and identified enablers and barriers. Methods: Databases were systematically searched for peer-reviewed studies. Interventions of interest were HIV services integrated with: neonatal/child services for children <5 years, hospital care of children <5 years, immunizations, and nutrition services. Outcomes of interest were: health outcomes of children <5 years, integrated services uptake, acceptability, and enablers and barriers. PROSPERO ID CRD42017082444. Results: Twenty-eight articles were reviewed: 25 (89%) evaluated the integration of HIV services into child health platforms, while three articles (11%) investigated the integration of child health services into HIV platforms. Studies measured health outcomes of children (n=9); service uptake (n=18); acceptability of integrated services (n=8), and enablers and barriers to service integration (n=14). Service integration had positive effects on child health outcomes, HIV testing, and postnatal service uptake. Integrated services were generally acceptable, although confidentiality and stigma were concerns Conclusion and Global Health Implications: Each clinical "touch point" with infants and children is an opportunity to provide comprehensive health services. In the current era of flat funding levels, integration of HIV and child health services is an effective, acceptable way to achieve positive child health outcomes. Key words: Africa, HIV, PITC • Child health services • PMTCT, neonatal health • Literature review • Immunization program Copyright © 2018 Smith et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.